Rancang Bangun Sistem Smart Locker Menggunakan Voice Access Berbasis Arduino Mega - Ferry Sudarto; Juni Aldo Zuntama; Ikbal Budiono (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
The importance of security makes everyone must ensure the security of everything that is included in him, both from the activities and assets he owns. The value of an asset has an incentive for everyone to implement a security system as protection. One of them is in the locker cabinet which generally still uses a manual locking system. So a Smart Locker is needed that uses microcontroller technology and a GSM Module combined with supporting applications such as Android-based. The purpose of this research is to design a security system with locker cabinet doors using Arduino Mega-based Voice Access. When the locker is forced to be opened, the buzzer will notify the owner that the locker door is opened via SMS short message remotely and the GSM module aims to open and lock the locker door via SMS message remotely where SMS communication mode uses the GSM module. Voice Access aims to make your access rights when you want to activate the locker system using the system voice command On and Off. Not everyone can use this locker because only a few can use it with the access given by entering the correct password when opening the locker door. The locker lock can be unlocked if the password is entered correctly, then the password is successful and then it will be stored and displayed on the LCD screen as an interface.